Multidye Biosorption: Wavelet Neural Network Modeling and Taguchi L16 Orthogonal Array Design. Issue 5 (18th April 2017) - Tabaraki, Reza; Khodabakhshi, Mina
Abstract : Biosorption of safranin (SF), malachite green (MG), and Janus green B (JG) onto Sargassum ilicifolium was studied in single and ternary systems. Principal component‐wavelet neural network was used for the simultaneous determination SF, MG, and JG in mixture. Biosorbent dose, pH and time were optimized by Taguchi L16 experimental design and optimum values were 0.1 g L −1, 8.5, and 85 min, respectively. The maximum biosorption capacity was 0.671 mmol g −1 . Kinetic, equilibrium and thermodynamic of the biosorption process were also investigated. The biosorption kinetic was described by pseudo‐second order model. Several isotherm models were fitted to experimental biosorption data and among the models, Hill, and Sips isotherms had the best fits. Negative Δ G° values confirmed the feasibility and spontaneous nature and of the biosorption process. Abstract : Biosorption of dyes by Sargassum ilicifolium is studied in single and ternary systems. Principal component‐wavelet neural network is used for simultaneous determination of safranin, malachite green, and janus green B in mixture. Taguchi L16 design is used for experimental optimization.